2000
DOI: 10.1007/bf01624617
|View full text |Cite
|
Sign up to set email alerts
|

Parental family variables and likelihood of divorce

Abstract: It has long been established that divorced men and women have substantially higher standardized general mortality than same gender persons. Because the incidence of divorce is increasing in many countries, determinants of divorce rates assume great importance as indirect risk factors for several diseases and conditions that adversely affect health. We have undertaken a study in Athens, Greece, to evaluate whether sibship size, birth order, and the gender composition of spousal sibships are related to the proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…On one hand, married individuals may be self-selected based on health-related characteristics, attitudes toward health, or behavioral factors, due to "marriage selection" [27]. On the other hand, literature in support of "marriage protection" implied that a protective role of spouses (especially women) providing physical and emotional support, resulted in better health [28]. Our findings showed that the total cost of inpatient of rural migrant workers with spouses was lower, and it supported the assertion that marital status is an important predictor of their health to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, married individuals may be self-selected based on health-related characteristics, attitudes toward health, or behavioral factors, due to "marriage selection" [27]. On the other hand, literature in support of "marriage protection" implied that a protective role of spouses (especially women) providing physical and emotional support, resulted in better health [28]. Our findings showed that the total cost of inpatient of rural migrant workers with spouses was lower, and it supported the assertion that marital status is an important predictor of their health to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Problem representation draws on the individual cognitive structure of self (Breckler, Pratkanis, & McCann, 1991) and culture as a cognitive system of knowledge and beliefs (Chikudate, 1991), and its variations may underlie the differences in problem-solving strategies between members in a marital dyad. As well as variations by age (Wu & Penning, 1997), birth order (Skalkidou, 2000), and gender (Heaton & Blake, 1999) in marital dysfunction, other factors such as region of birth (Chan & Heaton, 1989) have been shown to increase the risk of divorce petition. Marital breakdown rates are also likely to be affected by education (Jones, Asari, & Djuartika, 1994), religion (Sullivan, 2001), as well as length of marital stay (Booth, Johnson, White, & Edwards, 1986;Shiono & Quinn, 1994).…”
mentioning
confidence: 99%